THE INFLUENCE OF SEDIMENTATION ON SALINITY VARIATION IN THE EAST KUTAI BASIN, EAST KALIMANTAN, INDONESIA - Yuniardi, Yuyun; MOHAMAD, FEBRIWAN; Alfadli, Muhammad Kurniawan (Journal of Geological Sciences and Applied Geology, 2026)
The East Kutai Basin is a major deltaic system developed under strong river-dominated sedimentary processes, characterized by long-term progradation from marine to terrestrial environments. In such deltaic settings, salinity distribution is generally expected to show systematic lateral and vertical trends, with freshwater dominating proximal facies and saline water occurring in distal marine facies, while salinity commonly increases with depth due to depositional progradation through time. This study investigates lateral and vertical salinity variations in the East Kutai Basin and evaluates their relationship with sedimentary facies distribution. Salinity data were derived from both formation water analysis and apparent water resistivity (Rwa) calculations using resistivity logs based on Archie’s equation. These data were integrated with net sand maps and electrofacies interpretations to analyze salinity patterns across multiple stratigraphic layers. The results indicate that although the general lateral salinity trend from low salinity in channel facies to higher salinity in mouth bar facies is preserved, significant anomalies are present. Laterally, mouth bar deposits locally exhibit unexpectedly low salinity values, approaching those of channel facies. Vertically, salinity decreases with increasing depth in several stratigraphic groups, contradicting the expected progradational model. These anomalies are interpreted to result from lateral shifting of depositional environments due to progradation and expulsion of low-salinity compaction water from overpressured prodelta shale into adjacent sand bodies.